The Effectiveness of the Problem Based Learning Model Assisted by Interactive CD on Mathematical Problem Solving Ability Reviewed from Students' Cognitive Style - Marifatun, Marifatun; Sulistyorini, Sri; Ahmadi, Farid (Universitas Negeri Semarang, 2018)
This study was based on the low ability of mathematical problem solving in students of SMK Negeri 1 Dukuhturi, Tegal. The purpose of this study was (1) analyzing the effectiveness of the PBL Model assisted by Interactive CD in improving the ability to solve mathematical problems reviewed from the cognitive style of Vocational students, (2) analyzing mathematical problem solving ability reviewed from the cognitive style of FD of Vocational students in the PBL model assisted by Interactive CD, (3) analyzing the mathematical problem solving ability reviewed from the cognitive style of FI Vocational students in the PBL Model assisted by Interactive CD. The study used sequential explanatory mixed methods which were combination research methods that combine quantitative and qualitative research methods in sequence. The results showed that the average value of Post-test on students with PBL learning models assisted by interactive CD was 76. Meanwhile, the average score of Post-Test of students with interactive lecture learning was 70. The increased of the mathematical problems solving of the students achieve the classical completeness with a significance level of 0.05 obtained zvalue = 0.9901 < ztable = 2.035. The results of data reduction showed that FI students with PBL models assisted by CD Interactive had better mathematical problem-solving ability than FI students with interactive lectures. FD students with PBL models assisted by CD Interactive have better mathematical problem-solving ability than FD students with interactive lecture learning. This research can be used as an alternative to answering the problem-solving ability that occurs in mathematics learning.